2008
DOI: 10.1055/s-2007-963621
|View full text |Cite
|
Sign up to set email alerts
|

Kosteneinsparungspotenzial der Nadelbiopsie im Vergleich zur offenen Biopsie bei der Diagnose suspekter, nichtpalpabler Brustläsionen: Metaanalyse der Literatur und Vergleich mit Daten aus dem deutschen Sprachraum

Abstract: Use of CNBB as an alternative to OSB has the potential to substantially reduce healthcare costs. The data are based almost exclusively on the North American literature. A potential cost reduction in the Netherlands and Switzerland confirms these findings. Future work must include cost evaluation studies for German-speaking countries since this is an issue with important national economic ramifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…US-guided needle biopsy has become an accepted technique for diagnosis of breast abnormalities, and it may help patients avoid the higher morbidity and cost of surgical excision. The results indicated that the tissue number of biopsies acquired from CNB affected the histopathological results and biomarker status ( 11 , 20 ). The earlier study reported that it was more frequent for CNB to miss the components of invasive carcinoma because of the insufficient tissue ribbons, causing diagnosis underestimation.…”
Section: Discussionmentioning
confidence: 99%
“…US-guided needle biopsy has become an accepted technique for diagnosis of breast abnormalities, and it may help patients avoid the higher morbidity and cost of surgical excision. The results indicated that the tissue number of biopsies acquired from CNB affected the histopathological results and biomarker status ( 11 , 20 ). The earlier study reported that it was more frequent for CNB to miss the components of invasive carcinoma because of the insufficient tissue ribbons, causing diagnosis underestimation.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, node-negative and estrogen receptor positive breast cancer patients will be eligible for genetic profiling to determine their 21-gene recurrence score (OncotypeDx), and this information may also guide decisions regarding adjuvant chemotherapy in addition to endocrine therapy. 4-6 …”
Section: Discussionmentioning
confidence: 99%
“…Darum müssen diese Zahlen bei weiteren Adaptationen der OPS-Codes zu den DRG vor allem bei intensivpflichtigen Patienten berücksichtigt werden, zumal der Intensivtransport nicht als OPS-Leistung definiert ist, sondern lediglich als Mobilisierung eines intensivpflichtigen Patienten betrachtet wird. Detaillierte Kostenanalysen einzelner radiologischer Untersuchungen liegen in der uns bekannten Literatur nur vereinzelt vor[8,9]. Eine Studie der technischen Kosten der wichtigsten radiologischen Modalitäten (Konventionelles Röntgen, Sonografie, CT, MRT, Szintigrafie, Interventionelle Radiologie) aus dem Jahre 2000 analysiert die technischen Kosten für die jeweilige Modalität[1] durch Analyse der "Arbeitskosten" ("labor": Management, MTRA, Patientenbegleitdienst etc.)…”
unclassified